2005
DOI: 10.1038/sj.bjc.6602907
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in breast cancer mortality among French women: disappearing educational disparities from 1968 to 1996

Abstract: We investigated the time trends in social inequalities in breast cancer mortality with an analysis by age at death and birth cohort using a representative 1% sample of the French population and four subcohorts (1968 -1974, 1975 -1981, 1982 -1988 and 1990 -1996). Causes of death were obtained by direct linkage with the French national death registry. Education was measured at the beginning of each period, and educational disparities in breast cancer mortality were studied among women aged 35 -74 at the beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 17 publications
4
43
0
2
Order By: Relevance
“…Recent studies have suggested smaller educational differences in breast cancer mortality among younger women in many European populations (Martikainen and Valkonen, 2000;Menvielle et al, 2006;Strand et al, 2007). On the other hand, as southern European countries have still to experience the last stage of the smoking epidemic, higher lung cancer mortality rates among less-educated women may result there as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested smaller educational differences in breast cancer mortality among younger women in many European populations (Martikainen and Valkonen, 2000;Menvielle et al, 2006;Strand et al, 2007). On the other hand, as southern European countries have still to experience the last stage of the smoking epidemic, higher lung cancer mortality rates among less-educated women may result there as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicated a significant association between low SES and poorer cancer survival in Western countries, Australasia and Japan [9][10][11][12][13][14], while the contribution of specific causes to differences in mortality has been found to vary between countries. In recent years, at least three studies from the U.S. reported a poorer survival of pancreatic M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…People with a high socioeconomic status generally have better health in terms of both morbidity and mortality. Breast cancer, however, is more common among women with a high than a low socioeconomic status [1][2][3][4][5][6][7][8][9][10][11][12][13]. This atypical association is regarded as partly due to differences in reproductive and maternal behavior among women in these groups [1,6,10,11].…”
Section: Introductionmentioning
confidence: 99%